2004
DOI: 10.1086/422587
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Color of Welfare? How Whites’ Attitudes toward Latinos Influence Support for Welfare

Abstract: This article uses the National Election Study to consider how stereotypes about Latinos influence white support for welfare. It shows that whites' stereotypes about Latino work ethic grow more positive as the size of the Latino population increases, suggesting positive effects of contact. Moreover, the effect of whites' stereotypes about Latino-but not black-work ethic on support for welfare is contingent on ethnic context. In areas with few Latinos, the lazier whites think Latinos are, the less whites want to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
164
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(180 citation statements)
references
References 36 publications
12
164
1
3
Order By: Relevance
“…Other work finds little direct evidence of threat from Asian Americans and Hispanics (Cain, Citrin, and Wong 2000;Dixon and Rosenbaum 2004;Taylor 1998;Wong and Drake 2006) or finds threat only under specific economic, political, or spatial conditions (Branton and Jones 2005;Campbell, Wong, and Citrin 2006;Gay 2006;Oliver and Wong 2003). Still other studies have found that living near immigrants or Hispanics can actually reduce negative stereotyping (Fox 2004;Morris 1997, 1998). Threat operates in some cases, but certainly not in all.…”
Section: Beyond Realistic Conflictmentioning
confidence: 99%
“…Other work finds little direct evidence of threat from Asian Americans and Hispanics (Cain, Citrin, and Wong 2000;Dixon and Rosenbaum 2004;Taylor 1998;Wong and Drake 2006) or finds threat only under specific economic, political, or spatial conditions (Branton and Jones 2005;Campbell, Wong, and Citrin 2006;Gay 2006;Oliver and Wong 2003). Still other studies have found that living near immigrants or Hispanics can actually reduce negative stereotyping (Fox 2004;Morris 1997, 1998). Threat operates in some cases, but certainly not in all.…”
Section: Beyond Realistic Conflictmentioning
confidence: 99%
“…Scholarship on the American case reveals a negative relationship between racial and ethnic heterogeneity and welfare attitudes. Studies consistently show that diversity undermines support for social welfare (Fox 2004;Gilens 1999;Luttmer 2001). Related research finds a negative relationship between ethnoracial heterogeneity and social expenditure Easterly 1999, 2000;Hero 1998).…”
Section: Immigration and Welfare Attitudesmentioning
confidence: 99%
“…The "threat" hypothesis (Blalock 1967;Key 1949) suggests that the higher the percentage of nonwhites, the greater the support for more punitive policies. The "contact" hypothesis (Alport 1954;Fox 2004) indicates that the higher the percentage of nonwhites, the lower the support for punitive policies. There are also possible effects from an increased proportion of the population nonwhite enhancing minority political power (Keech [1968(Keech [ ] 1981.…”
Section: Figure 1 Predicted Probabilities By Race and Conditionmentioning
confidence: 99%